AGROECOLOGY AS A FOUNDATION IN COMMUNITY EMPOWERMENT THROUGH ECOLOGICAL VILLAGE SCHEMES IN BANGSAL VILLAGE OF OGAN KOMERING ILIR DISTRICT, INDONESIA - Rafa A.I.; Mulyanto; Sriati (Russian Journal of Agricultural and Socio-Economic Sciences, 2022)
The position of agroecology as the foundation for community empowerment provides a space for dialogue between the concepts of rural development. This space is manifested in an ecological village scheme related to efforts to save the environmet. This study aims to analyze the development of an ecological village and how agroecology is placed in the scheme of an ecological village. The research method used is descriptive qualitative method. The key informants in this study were six people consisting of two program implementers, two people from the Village Government, and two beneficiaries. Data collection techniques used: in-depth interviews, observations and document studies. The data analysis consists of five stages, namely preparing the data, reading, coding, analyzing, and presenting the data in a narrative report. Ecological village development is carried out based on local wisdom through a participatory and integrated process based on four main pillars, namely Governance of Land Tenure, Governance of Land use, Governance of production and Governance of consumption. The integration of these four pillars is necessary because of the interrelated relationships and influences each other as a system in a holistic scheme. The position of agroecology as the foundation for community empowerment has provided directions for social transformation where the important contribution of this empowerment program is the change from conventional farming systems to agroecology, increasing agroecology capacity, and developing market networks.